Cytotoxicity and Bonding Property of Bioinspired Nacre-like Ceramic-Polymer Composites - Sun, Hui; Gao, Kefeng; Yi, Zhe; Han, Chengwei; Liu, Zengqian; Wang, Qiang; Zhou, Qing; Zhang, Zhefeng (Frontiers in Bioengineering and Biotechnology, 2022)
For clinical applications, non-cytotoxicity and good bonding property of dental restorative materials are the most essential and important. The aim of this study was to evaluate the potential for clinical applications of two novel bioinspired nacre-like ceramic (yttria-stabilized zirconia)-polymer (polymethyl methacrylate) composites in terms of the cytotoxicity and bonding property. According to the results of cytotoxicity and proliferation experiments, the two composites were not cytotoxic to human periodontal ligament fibroblasts (HPDLFs) in vitro. Both composites exhibited improved bonding strength as compared to the control group (Vita In-Ceram YZ). As the polymer content in the composite material increases, its bonding strength also increases, which enhances the application potential of the material in the field of dental restoration. Meanwhile, by controlling the direction of loading force in the shear test, the effect of microstructure on the bonding strength of anisotropic composites was studied. The results showed that the loading direction had no significant effect on the bonding strength of the composite.